Adaptasi Teknologi Kahoot Sebagai Media Pembelajaran Matematika Sekolah Dasar - Ramadani, Aisyah; Exonetri, Dede; Erlia, Tiara Putriana; Putra, Zetra Hainul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This research focuses on helping students adapt to technology in the digital age. Learning media is continually evolving, and one notable example is the Kahoot application, which leverages existing technology. Kahoot is an interactive, game-based learning platform that actively engages students and encourages their participation in the learning process. To evaluate the effectiveness of Kahoot, the research was conducted with fourth-grade students using the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). A validator questionnaire was used to assess the application with feedback from 11 participants, who rated it as "good" and "very good". The researchers carefully analyzed the curriculum, instructional materials, and student needs in the process. The development of Kahoot quiz questions focused on Mathematics, specifically addressing stacked multiplication and small numbers. The trials involved six students organized into groups of two per team. Following the validity assessments and trials involving these students, it was concluded that the Kahoot application is indeed a suitable learning medium for educational purposes.